The Two Faces of Human Capital and their Effect on Technological Progress - López-Pueyo, Carmen; Barcenilla, Sara; Giménez, Gregorio (Panoeconomicus, 2018)
The aim of the paper is to investigate the effect of a new international estimate of human capital on the process of innovation and technology catch-up in developed countries. The new human capital variable is a measure of average human capital efficiency per hour worked that considers the role of both the quantity and quality of education. Our methodology is based on the framework proposed by Benhabib and Spiegel (2005) that uses a logistic function of technology diffusion. The analysis employs panel econometrics and tackles the endogeneity bias. Empirical results show robust evidence of the significance of this human capital variable as a driver of innovation and diffusion. The effects of cognitive skills on technological progress are higher the closer the economies are to the technology frontier. Furthermore, as technological progress has been measured using the improved TFP variables built in PWT 8.0, we confirm the existence of social returns to human capital.Key words: Human capital, Innovation, Technology diffusion, TFP growth.JEL: C33, J24, O47.Cilj rada je proučavanje uticaja nove međunarodne procene ljudskog kapitala na proces inoviranja i unapređenja tehnologije u razvijenim zemljama. Nova varijabla ljudskog kapitala je mera prosečne efikasnosti ljudskog kapitala po radnom satu, koja uzima u obzir kako nivo, tako i kvalitet obrazovanja. Naša metodologija je zasnovana na okvirima koji su predložili Benhabib i Spiegel (2005), a koji koristi logističku funkciju difuzije tehnologije. Prilikom analize koristimo ekonometriju panela i rešavamo pristrasnost endogenosti. Empirijski rezultati pokazuju robustan dokaz o značaju varijable ljudskog kapitala kao pokretača inovacija i difuzije. Efekti kognitivnih veština na tehnološki napredak su veći ukoliko su ekonomije bliže tehnološkoj granici. Štaviše, pošto je tehnološki napredak meren korišćenjem poboljšanih varijabli TFP ugrađenih u PWT 8.0, potvrđujemo postojanje socijalnih povrataka u ljudski kapital.Ključne reči: ljudski kapital, inovacija, difuzija tehnologije, rast TFP-a.